(untitled) (Global Journal of Human-Social Science, 2025)
This paper describes the method of teaching philosophy considering the Homework as the fundamental axis of this strategy as a basic nucleus in the teaching of philosophy also adapted to virtual distance or remote teaching To this end it identifies the two aspects of the teaching of philosophy the content formed by the concepts and the method as the Doing of philosophy this Doing is the philosophical act in such a way that the students exercise prepare or train themselves in the philosophical act without excluding the content of philosophy The task in the teaching of philosophy is fundamentally centred on the analysis of the philosophical text developed by the student during his classes or lessons the text of the analysis contains the philosophical concept and its execution develops the method of philosophy thus the Task in the teaching of philosophy addresses the content and the method in parallel or simultaneously as consubstantial and inseparable aspects of philosophy